2020
DOI: 10.1097/md.0000000000021507
|View full text |Cite
|
Sign up to set email alerts
|

Effect of non-invasive brain stimulation on neuropathic pain following spinal cord injury

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 38 publications
0
9
0
1
Order By: Relevance
“…By contrast, the synthesis results for the low frequencies (1 and 0.5 Hz) showed no difference or were mixed, meaning these intervention protocols may be less effective or inappropriate for some specific NPs. (3) The impact of the quality Galhardoni et al, 2015;Jin et al, 2015;Kumru et al, 2017;O'Connell et al, 2018*;Aamir et al, 2020;Liampas et al, 2020b;Moisset et al, 2020b;Yang and Chang, 2020;Zeng et al, 2020Onesti et al, 2013 Cragg et al, 2016;Gao et al, 2017;O'Connell et al, 2018*;Akyuz and Giray, 2019;Nardone et al, 2019;Aamir et al, 2020;Gatzinsky et al, 2020;Moisset et al, 2020b;Shen et al, 2020;Chang, 2020 Yilmaz et al, 2014*;Ma et al, 2015;Malavera et al, 2016;Choi and Chang, 2018 Lin et al, Kumar et al, 2009;Leung et al, 2009;Zaghi et al, 2011;Galhardoni et al, 2015;Chen et al, 2016;Gao et al, 2017;Kumru et al, 2017;Herrero Babiloni et al, 2018;O'Connell et al, 2018*;Gatzinsky et al, 2020;Moisset et al, 2020a;Yang and Chang, 2020Lefaucheur et al, 2004…”
Section: Discussion Principal Findings Of Evidence Mappingmentioning
confidence: 99%
“…By contrast, the synthesis results for the low frequencies (1 and 0.5 Hz) showed no difference or were mixed, meaning these intervention protocols may be less effective or inappropriate for some specific NPs. (3) The impact of the quality Galhardoni et al, 2015;Jin et al, 2015;Kumru et al, 2017;O'Connell et al, 2018*;Aamir et al, 2020;Liampas et al, 2020b;Moisset et al, 2020b;Yang and Chang, 2020;Zeng et al, 2020Onesti et al, 2013 Cragg et al, 2016;Gao et al, 2017;O'Connell et al, 2018*;Akyuz and Giray, 2019;Nardone et al, 2019;Aamir et al, 2020;Gatzinsky et al, 2020;Moisset et al, 2020b;Shen et al, 2020;Chang, 2020 Yilmaz et al, 2014*;Ma et al, 2015;Malavera et al, 2016;Choi and Chang, 2018 Lin et al, Kumar et al, 2009;Leung et al, 2009;Zaghi et al, 2011;Galhardoni et al, 2015;Chen et al, 2016;Gao et al, 2017;Kumru et al, 2017;Herrero Babiloni et al, 2018;O'Connell et al, 2018*;Gatzinsky et al, 2020;Moisset et al, 2020a;Yang and Chang, 2020Lefaucheur et al, 2004…”
Section: Discussion Principal Findings Of Evidence Mappingmentioning
confidence: 99%
“… Zhao et al (2020) found that 10 Hz rTMS over the hand area of the motor cortex could relieve acute CNP during the early stage of SCI. Some studies indicated that rTMS has no early pain relief after SCI but has a better intermediate analgesic effect compared with sham rTMS ( Shen et al, 2020 ). Regarding the management of intractable NP by rTMS in cases with SCI, Yılmaz et al (2014) found that the middle-term (over 6 weeks) analgesic effect of rTMS (10 Hz) was encouraging.…”
Section: Repetitive Transcranial Magnetic Stimulation For Central Neu...mentioning
confidence: 99%
“…The analgesic effect of tDCS was not superior to exercise alone after 12 sessions of intervention, and the beneficial effect was not maintained at follow-up ( Mehta et al, 2015 ; Yeh et al, 2021 ). However, not enough evidence could suggest that the analgesic effect of tDCS on NP following SCI over the M1 region is effective compared with medication treatments because of the lack of high-quality studies and sufficient sample size and control groups ( Boldt et al, 2014 ; Nardone et al, 2014 ; Mehta et al, 2015 ; Ngernyam et al, 2015 ; David et al, 2018 ; Shen et al, 2020 ; Li et al, 2021 ). Fagerlund et al (2015) found that pain reduction after the tDCS stimulation of the motor cortex was closely associated with increased peak spectral density in the θ-α range of electroencephalogram, but no corresponding association was found with sham stimulation.…”
Section: Transcranial Direct Current Stimulation For Central Neuropat...mentioning
confidence: 99%
“…Electrical and magnetic stimulation can serve as alternative methods to stimulate the nervous system and are currently more practical than chemogenetic stimulation from the clinical perspective. In fact, electrical and magnetic stimulation have already been tested in human subjects (Jo and Perez, 2020;Shen et al, 2020;Thomaz et al, 2019). Arguments have been made for the application of chemogenetic modulation as a treatment for neurological diseases, such as epilepsy (Desloovere et al, 2019;Hyder and Forcelli, 2020;Magnus et al, 2019), but there are several concerns that must be considered before this method can be applied in a clinical setting.…”
Section: Limitations Of the Studymentioning
confidence: 99%